Myasthenic Crisis in Eclampsia: A Case Report - Chanvitya Punthumapol (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Myasthenia gravis (MG) with eclampsia is a high risk condition. The use of magnesium sulfate to prevent seizure is contraindication because this may worsen MG and may develop myasthenic crisis. Myasthenic crisis results from weakness of upper airway muscles leading to obstruction and aspiration and / or weakness of respiratory muscles leading to reduced tidal volume. Termination of pregnancy, endotracheal intubation and mechanical ventilation, anticholinesterase drugs, corticosteroids, plasmapheresis, intravenous immunoglobulin and treatment of associated respiratory tract infections can improve the disease.